Dermoscopy of tumours arising in naevus sebaceous: a morphological study of 58 cases. (24th August 2015) - Zaballos, P.; Serrano, P.; Flores, G.; Bañuls, J.; Thomas, L.; Llambrich, A.; Castro, E.; Lallas, A.; Argenziano, G.; Zalaudek, I.; del Pozo, L.J.; Landi, C.; et al.
Abstract Background Naevus sebaceous is a congenital hamartoma commonly associated with the development of secondary neoplasms. There are sparse data relating to the dermoscopy of tumours arising in naevus sebaceous. Objectives To evaluate the dermoscopic features of a large series of neoplasms arising in naevus sebaceous. Methods Digital dermoscopic images of 58 histopathologically confirmed cases of secondary neoplasms arising in naevus sebaceous collected from 11 hospitals in Spain, France, Italy and Austria were evaluated for the presence of dermoscopic structures and patterns. Results The most frequent tumours collected were: trichoblastoma (39.6%), basal cell carcinoma (20.7%) and syringocystadenoma papilliferum (15.6%). The most remarkable findings were: (i) the pattern composed of asymmetrical large blue‐grey ovoid nests was more common in basal cell carcinomas than in trichoblastoma (58.3% vs. 4.3%; P < 0.001) and the pattern composed of a symmetrical total large blue‐grey ovoid nest (a blue‐grey homogeneous area which occupies the whole lesion) was more common in trichoblastoma (82.6% vs. 16.6%; P < 0.001); (ii) the most frequent pattern associated with syringocystadenoma papilliferum was a symmetric, erythematous lesion with exophytic papillary structures, ulceration and vessels (55.5%); (iii) the most common pattern associated with apocrine hidrocystomas was a total symmetric homogeneous area and arborizing telangiectasias (60%). Conclusions Benign adnexal tumours associated with naevus sebaceous are dermoscopic mimickers of basal cell carcinomas. A pigmented nodule arising in a naevus sebaceous with a total blue large ovoid nest on dermoscopy could be a trichoblastoma, basal cell carcinoma, hidrocystoma or hidradenoma. Dermoscopy can be a useful diagnostic tool which generates a more accurate preoperative diagnosis.